Water-Polymer Perturbation Characterization and Rules of Polymer Flooding in Offshore Heavy Oilfield. (22nd March 2021) - Liu, Yuyang; Kang, Xiaodong; Wei, Zhijie; Wang, Xudong; Zhang, Zhen
Abstract : Water injectors and polymer injectors coexist after well pattern infilling in some offshore oilfields, which exerts a deep impact on oil exploitation. In order to quantitatively characterize the injected water-polymer perturbation degree and analyze perturbation laws, water-polymer perturbation coefficient is proposed and established by comparing the displacement process of water-polymer coflooding and pure polymer flooding, which quantifies the dynamic change of displacement volume of injected water and polymer, and controlling strategy is discussed correspondingly to improve the development effect of water-polymer coflooding. Finally, a field case is used to demonstrate this new evaluation method. The results show that water-polymer perturbation coefficient has a good correlation with oil increasing, and water-polymer coflooding process can be divided into five stages according polymer perturbation coefficient. In addition, water-polymer coflooding has a better oil increasing effect than pure polymer flooding at the initial stage, but for a long period, development effect of pure polymer flooding is much better. The result has a great significance to quantitatively characterize water-polymer perturbation degree and make adjustment measurements.